Pour une protection de l'agriculture de l'UE sans barrières commerciales - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Dans son discours prononcé au Japon, le Commissaire Fischler ...